Clinical Outcomes Following Hemodynamic Parameter or Intravascular Imaging-Guided Percutaneous Coronary Intervention in the Era of Drug-Eluting Stents: An Updated Systematic Review and Bayesian Network Meta-Analysis of 28 Randomized Trials and 11,860 Patients - Hu, Meng-Jin; Tan, Jiang-Shan; Yin, Lu; Zhao, Yan-Yan; Gao, Xiao-Jin; Yang, Jin-Gang; Yang, Yue-Jin (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary angiography (CAG) is the standard imaging modality for guiding percutaneous coronary interventions (PCI). Intracoronary imaging techniques such as intravascular ultrasound (IVUS) and optical coherence tomography (OCT), and hemodynamic parameter like fractional flow reserve (FFR) can overcome some limitations of CAG. Objective We sought to explore the clinical outcomes of different PCI guidance modalities in the era of drug-eluting stent (DES). Methods A network meta-analysis of 28 randomized trials and 11,860 patients undergoing different modalities-guided PCI in the era of DES was performed. Odds ratio (OR) with 95% credible interval (CrI) were calculated. Results In comparison with CAG, IVUS was associated with a significant reduction in major adverse cardiovascular events (MACE, OR: 0.60; 95% CrI: 0.46–0.79), cardiovascular death (OR: 0.46; 95% CrI: 0.20–0.94), target vessel/lesion revascularization (TVR/TLR, OR: 0.55; 95% CrI: 0.41–0.74), and a trend toward decreased risk of stent thrombosis (OR: 0.44; 95% CrI: 0.17 to 1.00). FFR/quantitative flow ratio (QFR) could significantly reduce stroke compared with CAG, IVUS, and OCT/optical frequency domain imaging (OFDI). However, myocardial infarction (MI), all-cause death, stent thrombosis, and any revascularization presented similar risks for different PCI guidance modalities. Conclusion In the era of DES, IVUS led to lower risks of MACE than CAG, which was mainly due to lower risks of cardiovascular death and TVR/TLR. A trend toward decreased risk of stent thrombosis was also observed with IVUS. Hemodynamic parameter (FFR/QFR)-guided PCI could significantly reduce the stroke risk compared with CAG, IVUS, and OCT/OFDI. Systematic Review Registration [https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42021291442].